2011
DOI: 10.1212/wnl.0b013e31820e7b74
|View full text |Cite
|
Sign up to set email alerts
|

Progressive regional atrophy in normal adults with a maternal history of Alzheimer disease

Abstract: Objective: Beyond age, having a family history is the most significant risk factor for Alzheimer disease (AD). This longitudinal brain imaging study examines whether there are differential patterns of regional gray matter atrophy in cognitively healthy elderly subjects with (FHϩ) and without (FHϪ) a family history of late-onset AD.Methods: As part of the KU Brain Aging Project, cognitively intact individuals with a maternal history (FHm, n ϭ 11), paternal history (FHp, n ϭ 10), or no parental history of AD (FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
86
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 39 publications
7
86
1
Order By: Relevance
“…The relative consistency of these FH findings across diverse neuroimaging modalities 4,[7][8][9]11 suggests that FH is a prominent, even if nonspecific, risk factor for AD perhaps embodying an array of genetic and environmental indices that remain to be fully elucidated. 10,22 Contrary to prior reports suggesting that maternal history of AD might confer a greater risk of ADrelated cerebral abnormalities than paternal history of AD, 5,7,8,18,23 we found that pFHϩ subjects were just as likely as mFHϩ subjects to experience atrophy of the posterior hippocampus. This observation suggests that, in our cohort, the FH effect was not driven by a particular parent of origin.…”
Section: Results Demographic Findingscontrasting
confidence: 99%
See 3 more Smart Citations
“…The relative consistency of these FH findings across diverse neuroimaging modalities 4,[7][8][9]11 suggests that FH is a prominent, even if nonspecific, risk factor for AD perhaps embodying an array of genetic and environmental indices that remain to be fully elucidated. 10,22 Contrary to prior reports suggesting that maternal history of AD might confer a greater risk of ADrelated cerebral abnormalities than paternal history of AD, 5,7,8,18,23 we found that pFHϩ subjects were just as likely as mFHϩ subjects to experience atrophy of the posterior hippocampus. This observation suggests that, in our cohort, the FH effect was not driven by a particular parent of origin.…”
Section: Results Demographic Findingscontrasting
confidence: 99%
“…For example, recent cross-sectional 18 and longitudinal 5 studies have found evidence for GM volume reductions in AD-susceptible brain regions, such as the precuneus, among cognitively intact FHϩ individuals relative to FHϪ peers. Our study extends these findings 5,18 by using a considerably larger sample, implementing a longer follow-up, and, more importantly, showing that FH-related hippocampal atrophy is present at a relatively young age (our cohort's mean baseline age was 54 years). The relative consistency of these FH findings across diverse neuroimaging modalities 4,[7][8][9]11 suggests that FH is a prominent, even if nonspecific, risk factor for AD perhaps embodying an array of genetic and environmental indices that remain to be fully elucidated.…”
Section: Results Demographic Findingssupporting
confidence: 75%
See 2 more Smart Citations
“…It remains to be established whether Ab accumulation is also an early event in LOAD. 1 Previous brain imaging studies have shown that, among NL individuals who have parents with LOAD, those with maternal FH (FHm) present with increased Ab load on 11 C-Pittsburgh compound B (PiB)-PET, 11,12 progressive glucose metabolism reductions on 18 F-fluoro-2-deoxyglucose (FDG)-PET, 13,14 and gray matter volume (GMV) loss on MRI [15][16][17][18] in the same regions as those with clinical AD. In contrast, NL individuals with paternal FH (FHp) are far less likely to show biomarker abnormalities.…”
mentioning
confidence: 99%